(untitled) - Bell, Daniel (New York, 1973)
Contents: From Industrial to Post-Industrial Society: Theories of Social Development; From Goods to services: The Changing Shape of the Economy; The Dimensions of Knowledge and Technology: The New Class Structure of Post-Industrial Society
Keywords: Social history,Social prediction,Lịch sử xã hội,Dự đoán xã hội; 20th century,Thế kỷ 20